Why are the wages of job stayers procyclical? - Donggyun Shin; Kwanho Shin (Osaka University, Institute of Social and Economic Research (ISER), 2003)
This paper explains how real wages are procyclical for those who stay with the same employer. On the basis of the Panel Study of Income Dynamics data for the period of 1974-75 to 1990-91, we find that the substantial wage procyclicality among job stayers is mostly accounted for by great wage adjustments during the period when the unemployment rate reaches a historical minimum level from the start of the employee's current job. This finding explains how the real wages of job stayers behave asymmetrically over the cycle and more importantly how the evidence of stayers' great wage procyclicality accords with the theoretical prediction of implicit contracts that stresses costless mobility.
Keywords: E24; E32; 330; Reallohn; Konjunktur; Betriebszugehörigkeit; USA